Saccharomyces cerevisiae Heat Shock Transcription Factor Regulates Cell Wall Remodeling in Response to Heat Shock - Imazu, Hiromi (American Society for Microbiology, 2005)
The heat shock transcription factor Hsf1 of the yeast Saccharomyces cerevisiae regulates expression of genes encoding heat shock proteins and a variety of other proteins as well. To better understand the cellular roles of Hsf1, we screened multicopy suppressor genes of a temperature-sensitive hsf1 mutation. The RIM15 gene, encoding a protein kinase that is negatively regulated by the cyclic AMP-dependent protein kinase, was identified as a suppressor, but Rim15-regulated stress-responsive transcription factors, such as Msn2, Msn4, and Gis1, were unable to rescue the temperature-sensitive growth phenotype of the hsf1 mutant. Another class of suppressors encoded cell wall stress sensors, Wsc1, Wsc2, and Mid2, and the GDP/GTP exchange factor Rom2 that interacts with these cell wall sensors. Activation of a protein kinase, Pkc1, which is induced by these cell wall sensor proteins upon heat shock, but not activation of the Pkc1-regulated mitogen-activated protein kinase cascade, was necessary for the hsf1 suppression. Like Wsc-Pkc1 pathway mutants, hsf1 cells exhibited an osmotic remedial cell lysis phenotype at elevated temperatures. Several of the other suppressors were found to encode proteins functioning in cell wall organization. These results suggest that Hsf1 in concert with Pkc1 regulates cell wall remodeling in response to heat shock.